METHODS OF DETERMINATION OF THE DRESSING FASTNESS - O. S. Komarov; K. E. Baranovsky; E. V. Rosenberg; T. D. Komarova (Литьë и металлургия)
The method of determination of durability of paints after heating up to various temperatures by the value of hardness of coverings is offered.